Supply Chain Risk Management Methods in the Process Of Formation of Advertising Campaign - Hassan Ali Al-Ababneh; Mahmud Agel Abu Dalbouh (International Journal of Supply Chain Management, 2020)
Abstract- The possibilities for applying supply chain risk management methods in the development of an advertising campaign are examined. The conceptual features of the implementation of promotional activities in the modern context are highlighted. A system-structural analysis, which enabled to develop an author's classification of the main types of risks and methods of their management in the process of forming an advertising company under conditions of uncertainty, is carried out. Based on a critical analysis of structured approaches to supply chain risk management methods, a ranking of supply chain risk management methods with features of advertising and advertising investment is proposed. A ranked list of supply chain risk management methods is developed for their prompt application in the development of an advertising company. In the process of solving the stated problems, the basic scientific approaches to the classification of supply chain risk management methods were analyzed, both standard methods (ISO 31000) and practical and creative practices of management were investigated. The synthesis of theoretical data and their systematization through a critical rethinking and analysis of supply chain risk management practices made it possible to develop and present an author’s interpretation of a generalized classification of supply chain risk management methods. The ranking of the main methods for assessing and managing risks for the formation of an advertising company, taking into account its features, is classified and performed.